The Regulation of Spermatogonial Stem Cells in an Adult Testis by Glial Cell Line-Derived Neurotrophic Factor - Wright, William W. (Frontiers in Endocrinology, 2022)
This review focuses on the in vivo regulation of spermatogonial stem cells (SSCs) in adult testes by glial cell line-derived neurotrophic factor (GDNF). To study adult mouse testes, we reversibly inhibited GDNF stimulation of SSCs via a chemical-genetic approach. This inhibition diminishes replication and increases differentiation of SSCs, and inhibition for 9 days reduces transplantable SSC numbers by 90%. With more sustained inhibition, all SSCs are lost, and testes eventually resemble human testes with Sertoli cell-only (SCO) syndrome. This resemblance prompted us to ask if GDNF expression is abnormally low in these infertile human testes. It is. Expression of FGF2 and FGF8 is also reduced, but some SCO testes contain SSCs. To evaluate the possible rebuilding of an SSC pool depleted due to inadequate GDNF signaling, we inhibited and then restored signaling to mouse SSCs. Partial rebuilding occurred, suggesting GDNF as therapy for men with SCO syndrome.